Animal models of Takotsubo syndrome: bridging the gap to the human condition - Zulfaj, Ermir; Nejat, AmirAli; Haamid, Abdulhussain; Elmahdy, Ahmed; Espinosa, Aaron; Redfors, Björn; Omerovic, Elmir (Frontiers in Cardiovascular Medicine, 2024)
Modelling human diseases serves as a crucial tool to unveil underlying mechanisms and pathophysiology. Takotsubo syndrome (TS), an acute form of heart failure resembling myocardial infarction, manifests with reversible regional wall motion abnormalities (RWMA) of the ventricles. Despite its mortality and clinical similarity to myocardial infarction, TS aetiology remains elusive, with stress and catecholamines playing central roles. This review delves into current animal models of TS, aiming to assess their ability to replicate key clinical traits and identifying limitations. An in-depth evaluation of published animal models reveals a variation in the definition of TS among studies. We notice a substantial prevalence of catecholamine-induced models, particularly in rodents. While these models shed light on TS, there remains potential for refinement. Translational success in TS research hinges on models that align with human TS features and exhibit the key features, including transient RWMA. Animal models should be comprehensively evaluated regarding the various systemic changes of the applied trigger(s) for a proper interpretation. This review acts as a guide for researchers, advocating for stringent TS model standards and enhancing translational validity.